Infrastructure and Educational Outcomes in Bolivia - Antonio N. Bojanic; Mauricio Foronda; Alejandro Jordán (Revista Latinoamericana de Estudios Educativos)
This article analyzes how the levels of enrollment, promotion, dropout and failure are affected by access to basic infrastructure services such as electricity, drinking water, and sanitation services, as well as by access to basic facilities such as classrooms, sports fields, laboratories, libraries, and computer rooms. Based on Bolivian data for the entire universe of schools and colleges at the preschool, primary, and secondary levels, an empirical study was carried out on the impact of educational infrastructure during the period 2015-2020. It is analyzed whether the results vary depending on whether the schools are public, are located in urban centers and whether they offer a humanistic degree. Consistently, the findings show that access to basic infrastructure can play a fundamental role in generating positive educational outcomes, but when the analysis is disaggregated by geographic region and educational levels, there emerge significant differences.